A comparison of two types of ankle supports in men with haemophilia and unilateral ankle pain from arthropathy. Issue 3 (20th February 2017) - Oleson, D.; Fox, L.; Nguyen, T.; Sochacki, P.; McCarthy, M.; Adams, E.; Recht, M.
Abstract : Introduction: Adults with haemophilia frequently have a painful and disordered gait due to ankle arthropathy. Aim: The aim of this study was to determine if pain and gait parameters were affected by the use of different types of ankle bracing. Methods: We investigated the gait patterns of 17 men with severe haemophilia without bracing, using a fracture boot (FB) and a carbon fibre floor reaction ankle foot orthosis (CF‐AFO). Pain relief was determined in each condition. Gait parameters were measured by means of an electronic, pressure sensitive mat. Results: Both brace types relieved pain. Use of a FB altered gait parameters that are associated with movement of the involved and the uninvolved limb during the gait cycle, whereas the use of a CF‐AFO did not affect the gait cycle. Conclusion: This study suggests that pain relief from both types of braces is identical but use of a CF‐AFO does not alter gait patterns.